Antioxidant dietary fibre recovery from Brazilian Pinot noir grape pomace. (15th June 2016) - Beres, Carolina; Simas-Tosin, Fernanda F.; Cabezudo, Ignacio; Freitas, Suely P.; Iacomini, Marcello; Mellinger-Silva, Caroline; Cabral, Lourdes M.C.
Highlights: Dietary fibre was recovered from grape pomace via hot water extraction. Polysaccharides were identified as pectic and glucose-based polymers. Phenolics were mainly identified as catechin, gallic acid and epicatechin. Extracts had ABTS radical scavenging capacity, suggesting antioxidant capacity. Extracts rich in antioxidant dietary fibre have a potential use as food ingredients. Abstract: Brazilian grape pomace was extracted in hot water, and a factorial experiment was used to evaluate polysaccharide recovery. The dependent variables were the temperature, particle size and solute:solvent ratio. Polysaccharide yields varied from 3% to 10%, and the highest sugar content was observed when extraction was carried out at 100 °C from finely sized particles (⩽249 μm) in a 1:12 solute:solvent ratio. The monosaccharide composition of extracts obtained from flours were, on average, Rha:Ara:Xyl:Man:Gal:Glc:GalA in a 3:32:2:13:11:20:19 M ratio, with varying Glc:GalA ratios. 13 C NMR and HSQC spectra confirmed the presence of pectic- and glucose-based polysaccharides in the extracts. Phenolic compounds were found after pomace extraction, and catechin, gallic acid and epicatechin were the principal compounds identified. The extracts also had ABTS radical scavenging capacity (from 8.00 to 46.60 mMol Trolox/100 g pomace). These findings indicate that these grape pomace flours are rich in antioxidant dietary fibre and have a potential use as food ingredients.